Nb2C MXene-Functionalized Scaffolds Enables Osteosarcoma Phototherapy and Angiogenesis/Osteogenesis of Bone Defects - Yin, Junhui; Pan, Shanshan; Guo, Xiang; Gao, Youshui; Zhu, Daoyu; Yang, Qianhao; Gao, Junjie; Zhang, Changqing; Chen, Yu (Nano-Micro Letters, 2021)
Early surgical resection and chemotherapy of bone cancer are commonly used in the treatment of bone tumor, but it is still highly challenging to prevent recurrence and fill the bone defect caused by the resection site. In this work, we report a rational integration of photonic-responsive two-dimensional (2D) ultrathin niobium carbide (Nb2C) MXene nanosheets (NSs) into the 3D-printed bone-mimetic scaffolds (NBGS) for osteosarcoma treatment. The integrated 2D Nb2C-MXene NSs feature specific photonic response in the second near-infrared (NIR-II) biowindow with high tissue-penetrating depth, making it highly efficient in killing bone cancer cells. Importantly, Nb-based species released by the biodegradation of Nb2C MXene can obviously promote the neogenesis and migration of blood vessels in the defect site, which can transport more oxygen, vitamins and energy around the bone defect for the reparative process, and gather more immune cells around the defect site to accelerate the degradation of NBGS. The degradation of NBGS provides sufficient space for the bone remodeling. Besides, calcium and phosphate released during the degradation of the scaffold can promote the mineralization of new bone tissue. The intrinsic multifunctionality of killing bone tumor cell and promoting angiogenesis and bone regeneration makes the engineered Nb2C MXene-integrated composite scaffolds a distinctive implanting biomaterial on the efficient treatment of bone tumor. Highlights: 1 2D Nb2C MXene-integrated 3D-printing scaffolds against osteosarcoma were constructed with theragenerative functionality. 2 Nb2C MXene in 3D scaffolds enabled photothermal ablation of osteosarcoma at NIR-II biowindow. 3 Nb2C MXene in 3D scaffolds promoted osteogenesis, osteoconduction and osteoinduction, and drove vascularization for bone regeneration.